NOUA PEDAGOGIE OFERITĂ DE WEB 2.0 - USM ADMIN (Moldova State University, 2011)
Education is important in any society, because education level determines the standard of living and per capita income. In turn, national education systems heavily depend on the culture of information, effective use of ICT, which support four large areas in modern education: the place, time, schedule, personification. This work presents an overview of synthesis between educational technologies of eLearning based on Web 2.0 and Personal Learning Environment (new pedagogy offered by web2.0), as one of the newest trends in eLearning.